Efficacy of Pazopanib in the Treatment of Metastatic Malignant Giant Cell Tumor of Soft Tissue: A Case Report - Tadashi Iwai; Naoto Oebisu; Manabu Hoshi; Naoki Takada; Hiroaki Nakamura (Current Oncology, 2022)
Giant cell tumor of soft tissue (GCT-ST), histologically resembling the GCT of the bone, is a rare tumor. The tumor has been categorized to have low malignancy. Few reports of local recurrence or distant metastasis and the use of chemotherapeutic agents for metastatic GCT-ST exist. Herein, we report the efficacy of pazopanib in a 78-year-old Japanese woman with GCT in the intrinsic back musculature with both post-operative local recurrence and lung metastasis. The patient visited the hospital with a three-month history of a palpable mass in the intrinsic back musculature. Following magnetic resonance imaging, the tumor predominantly exhibited slight hyperintensity on T2-weighted images and intense heterogeneous enhancement on contrast-enhanced T1-weighted images. A percutaneous needle biopsy was performed, and the pathological diagnosis was GCT-ST. The patient underwent surgery, and three months later she presented with not only local recurrence but also multiple lung metastases. The patient was immediately treated with pazopanib 400 mg once daily. One month after initiating treatment, a partial response in the pulmonary lesions was observed, and stable disease (SD) effects lasted for 11 months without severe adverse effects. Therefore, pazopanib treatment for metastatic malignant giant cell tumor of soft tissue achieved reasonable success.